Kentucky bluegrass growth under saline, waterlogging, and saline‐waterlogging conditions during germination and seedling growth. Issue 1 (23rd February 2020) - Rue, Kevin; Zhang, Qi
Abstract: Salinity and waterlogging, two major problems in turfgrass management, often co‐occur in nature; however, information on the response of turfgrass to the combined salinity‐waterlogging stress is limited. The objective of this study was to determine growth response of nine Kentucky bluegrass ( Poa pratensis L.) cultivars to the control (i.e., non‐stress), salinity, waterlogging, and the combined salinity‐waterlogging stress during the germination and seedling stage (six weeks) in pots in a greenhouse. Data including shoot and root dry weight, root‐to‐shoot dry weight ratio, root length, and specific root length were analyzed. Salinity‐waterlogging reduced dry weight of both shoots (556.1 mg) and roots (269.4 mg) compared with the controls (1295.1 and 686.7 mg) ( P  < .0001). The control plants had a root‐to‐shoot dry weight ratio of 52.9%, higher than the salinity‐treated ones (44.1%) ( P  = .0017). Root length was higher in the control and waterlogged plants than salinity and salinity‐waterlogged plants. Saline‐waterlogged and control plants had the highest and lowest specific root length, respectively. Among the Kentucky bluegrass cultivars, Sudden Impact, Award, Limousine, and Kenblue had higher tissue biomass, followed by America, Legend, and Arrowhead, whereas Moonlight and Blue Note performed poorly. Blue Note had a higher specific root length than all other grasses, except Moonlight. It may be a better management practice to use cultivars such as Sudden Impact, Award, Limousine, and Kenblue, which appear from this research to be relatively tolerant to salinity/waterlogging stress, when establishing a new turf surface under the aforementioned stresses.